2018
DOI: 10.1080/13685538.2018.1432586
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lower urinary tract symptoms/benign prostatic hyperplasia and erectile dysfunction

Abstract: This article summarizes years of challenging research on erectile dysfunction (ED), a condition that has an important social and cultural relevance. Preclinical and clinical research progress has led to new therapeutic approaches to ED in patients with different comorbidities and particularly in those with low urinary tract symptoms (LUTS)/benign prostatic hyperplasia (BPH). These goals were possible only by combined work of specialists and researchers of different and intertwined medical disciplines. Currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…ED has been linked to LUTS/BPH as a part of this syndrome. LUTS/BPH and ED share similar pathogenetic mechanisms such as chronic inflammation, vascular dysfunction, and hormonal alterations (Calogero, Burgio, Condorelli, Cannarella, & La Vignera, 2018, 2019). Exacerbations of LUTS are often accompanied by worsening of the IIEF-5 index.…”
Section: Discussionmentioning
confidence: 99%
“…ED has been linked to LUTS/BPH as a part of this syndrome. LUTS/BPH and ED share similar pathogenetic mechanisms such as chronic inflammation, vascular dysfunction, and hormonal alterations (Calogero, Burgio, Condorelli, Cannarella, & La Vignera, 2018, 2019). Exacerbations of LUTS are often accompanied by worsening of the IIEF-5 index.…”
Section: Discussionmentioning
confidence: 99%
“…Cavernous muscle cells express α-adrenergic receptors and, once activated by the sympathetic neurotransmitters, they lead to arterial smooth muscle contraction and hinder penile erection. Several lines of evidence support the negative impact of anxiety on sexual performance and erectile function [4][5][6], and this negative influence is widely accepted [3,7].…”
Section: Introductionmentioning
confidence: 96%
“…2,3 The combined prevalence of BPH is approximately 26.2% at the world level. 1 This condition triggers pressure on the urethra causing bladder outflow obstruction, and hence a variability of lower urinary tract symptoms (LUTS).…”
Section: Introductionmentioning
confidence: 99%
“…1 This condition triggers pressure on the urethra causing bladder outflow obstruction, and hence a variability of lower urinary tract symptoms (LUTS). 2,3 The combined prevalence of BPH is approximately 26.2% at the world level. 4 It is also reported that BPH increases with age and affect more than 70% of elderly males.…”
Section: Introductionmentioning
confidence: 99%